IDENTIFIKASI LOKASI POTENSIAL UNTUK PEMENUHAN RUANG TERBUKA HIJAU (RTH) PUBLIK AKTIF DI KOTA SALATIGA - Martha Rosdiana Utami; Retno Susanti (TATALOKA, 2019)
The condition of Green Open Space (or Open Space) in Salatiga City has not reached the minimum standard of 30%, as the public Open Space in this City was still 5.61%, and Private Open Space was 6.4%. Active Public Open Spaces were distributed in three sub districts. Minister of Public Work’s Regulation Number05/PRT/M/2008 about guidelines of Open Space providing and utilization in urban area mentions that active public open space should provide at least a park for each of administration at smallest scale of RT (neighborhood association), RW (citizens associations), Kelurahan, Sub District and City. For that reason, identification should be made on the potential location to be developed into active public open space. The compatibility of Open Space location was analyzed using Weighted Overlay analysis taking Percent of Influence value or weight with Analytic Hierachy Proccess (AHP) method to 4 exspert . The result of analysis was the map of compatibility of active public Open Space location with respective width of 26,12 % for compatible class, 59,27% for adequate class, and 12,54 % for incompatible class. This research is a new research, because the final result of determining the location of Active Public RTH in the form of 29 points of location of government-owned land using intersect analysis on GIS. This study is a follow-up for the Salatiga City government to create a disincentive policy related to the fulfillment of KDH, such as the imposition of taxes and compensation that can be used to replace green land that the government can provide.